Single-cell stabilization method identifies gonadotrope transcriptional dynamics and pituitary cell type heterogeneity. Issue 21 (24th October 2018) - Ruf-Zamojski, Frederique; Ge, Yongchao; Nair, Venugopalan; Zamojski, Michel; Pincas, Hanna; Toufaily, Chirine; Tome-Garcia, Jessica; Stoeckius, Marlon; Stephenson, William; Smith, Gregory R; Bernard, Daniel J; Tsankova, Nadejda M; et al.
Abstract: Immediate-early response genes (IEGs) are rapidly and transiently induced following an extracellular signal. Elucidating the IEG response patterns in single cells (SCs) requires assaying large numbers of timed samples at high accuracy while minimizing handling effects. To achieve this, we developed and validated RNA stabilization B uffer for E xamination of S ingle-cell T ranscriptomes (RNA-Best), a versatile single-step cell and tissue preservation protocol that stabilizes RNA in intact SCs without perturbing transcription patterns. We characterize for the first time SC heterogeneity in IEG responses to pulsatile gonadotropin-releasing hormone (GnRH) stimuli in pituitary gonadotrope cells. Our study identifies a gene-specific hierarchical pattern of all-or-none transcript induction elicited by increasing concentrations of GnRH. This quantal pattern of gene activation raises the possibility that IEG activation, when accurately resolved at the SC level, may be mediated by gene bits that behave as pure binary switches.